Heterotrimeric G proteins in the control of parathyroid hormone actions - (:unkn) unknown (BIOSCIENTIFICA LTD, 2017)
Parathyroid hormone (PTH) is a key regulator of skeletal physiology and calcium and phosphate homeostasis. It acts on bone and kidney to stimulate bone turnover, increase the circulating levels of 1,25 dihydroxyvitamin D and calcium and inhibit the reabsorption of phosphate from the glomerular filtrate. Dysregulated PTH actions contribute to or are the cause of several endocrine disorders. This calciotropic hormone exerts its actions via binding to the PTH/PTH-related peptide receptor (PTH1R), which couples to multiple heterotrimeric G proteins, including G(s) and G(q/11). Genetic mutations affecting the activity or expression of the alpha-subunit of G(s), encoded by the GNAS complex locus, are responsible for several human diseases for which the clinical findings result, at least partly, from aberrant PTH signaling. Here, we review the bone and renal actions of PTH with respect to the different signaling pathways downstream of these G proteins, as well as the disorders caused by GNAS mutations.
Keywords: PTH; G proteins; GNAS; bone; kidney; STIMULATORY G-PROTEIN; PSEUDOHYPOPARATHYROIDISM TYPE-IB; XL-ALPHA-S; MCCUNE-ALBRIGHT-SYNDROME; OSTEOCLAST DIFFERENTIATION FACTOR; IDENTIFIES PDE4D MUTATIONS; MESSENGER-RIBONUCLEIC-ACID; IMPRINTING CONTROL ELEMENT; NA+ PHOSPHATE COTRANSPORT; FGF23 GENE-EXPRESSION